Comparison of efficacy and safety of tacrolimus and methotrexate in combination with abatacept in patients with rheumatoid arthritis; a retrospective observational study in the TBC Registry. Issue 6 (8th September 2015) - Fujibayashi, Takayoshi; Takahashi, Nobunori; Kida, Daihei; Kaneko, Atsushi; Hirano, Yuji; Fukaya, Naoki; Yabe, Yuichiro; Oguchi, Takeshi; Tsuboi, Seiji; Miyake, Hiroyuki; Takemoto, Toki; Kawasaki, Masashi; et al.
Abstract : Objectives. Tacrolimus (TAC) and abatacept (ABT) inhibit T-cells via different mechanisms and, in combination, may be effective against rheumatoid arthritis. However, they may also disrupt normal immune functions. We compared the efficacy and safety of ABT administered to patients in combination with TAC, methotrexate (MTX), or other drugs. Methods. This was a retrospective multicenter study conducted to compare the efficacy and safety of ABT in 211 patients: the drug was administered together with TAC (ABT+ TAC group; 22 patients), MTX (ABT+ MTX group; 102 patients), or patients treated without concomitant MTX or TAC (ABT mono group; 87 patients). The disease activity, treatment continuation rate, and reason for discontinuation of treatment were investigated. Results. The retention rate at Week 24 was similar in the three groups. There were no cases of discontinuation related to the appearance of adverse events in the ABT+ TAC group. At Week 24, according to the European League Against Rheumatism response criteria, the "good" response rates were 33.3%, 13.4%, and 13.4% in the ABT+ TAC, ABT+ MTX, and ABT mono groups, respectively. Statistically significant decreases in various disease activity scores/indices were observed in all the groups as early as Week 4. Conclusions. Although the sample size was small, the results of this retrospective study suggest that the ABT+ TAC combination therapy has at least comparable safety and efficacy to those of the ABT+ MTX combination, and that it can thus be a useful option for patients who cannot take MTX.